2020
DOI: 10.1155/2020/8140782
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Nonlinear Stiffness of Rubber Pad under Different Temperatures and Prepressures

Abstract: The static stiffness of rubber springs is affected by temperature and prepressure. In this thesis, the relationship between Young’s modulus and temperature of rubber was studied, and the quantitative relationship between them was determined. The approximate formula for calculating the static stiffness of rubber pads was further modified, and the ellipse approximation method and convexity coefficient correction method were proposed. In addition, the influence of temperature on geometric nonlinearity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In general, the deformation of the rail pads increased as the temperature increased. This in line with the results of Xu et al [45] and Liu et al [46]. From the observation, deformation of the EVA material increased gradually as temperature increased over the entire range of 0-60 °C.…”
Section: Effect On Temperaturesupporting
confidence: 92%
“…In general, the deformation of the rail pads increased as the temperature increased. This in line with the results of Xu et al [45] and Liu et al [46]. From the observation, deformation of the EVA material increased gradually as temperature increased over the entire range of 0-60 °C.…”
Section: Effect On Temperaturesupporting
confidence: 92%
“…• Temperature is another variable influencing the dynamic behaviour of rubber. [7][8][9][10][11] It also conditions the deterioration of its properties. • Variation with time and ageing: the deterioration of rubber depends on its working conditions but also on time.…”
Section: Introductionmentioning
confidence: 99%
“…Creep is the irrecoverable residual deformation that remains in a component after being subjected to a constant stress for a period of time, while recovery is the measure of the original dimension recovery of the rubber after strain release.• Temperature is another variable influencing the dynamic behaviour of rubber. 711 It also conditions the deterioration of its properties.• Variation with time and ageing: the deterioration of rubber depends on its working conditions but also on time. Moreover, it is already difficult from the manufacturing process to control the properties of rubber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where: P specific power, ω is frequency, ε A is strain percentage and E 00 is loss modulus. 38 The relationship between Young's modulus and the temperature of rubber was studied, and the quantitative relationship between them was determined by Xu et al 39 Elastomeric pads used with the three-piece freight bogies are sand-witch shaped and consist of three metal plates having rubber/elastomeric elements in between. It has been observed that the sand-witch design of the EM pad meets the desired deflection characteristics in static conditions but in long continuous service, the pad exhibits excessive movement between the top and bottom plates due to softening of the rubber element at elevated temperatures as a result of hysteresis heat generation.…”
Section: Introductionmentioning
confidence: 99%